ANALISA POTENSI LONGSOR MENGGUNAKAN DATA MIKROTREMOR DAN KEMIRINGAN DI JALAN RAYA PUNCAK KABUPATEN BOGOR - Kusuma, Rendi Wijaya; Pratama, Wahyudi Nasrul (Pusdiklat BMKG, 2020)
Bogor Regency is an area where landslides often occur. The factors that cause the landslides are meteorological factor likes rainfall and geological factors due to texture, rock structures surface lithology and slope. This studyaims to map area that has high potential to occur landslide based on indicator Ground Shear Strain (G) valueand soil characteristics in Jalan Raya Puncak Bogor, Bogor Regency using Horizontal to Vertical Sprectral Rasio(HVSR) method by considering slope factor on the measurement points. The measurements were carried out usingAccelerometer sensor at 21 measurement points with a spacing of 700-1000 m and data recording for 30 minutes.The distribution of landslide potential locations are classified into high, medium, low and no potential. P15, P18 and P21 measurement points had values G=3.3510 to 1.1010 with soft soil character and steep enough to steep slope were classified as areas that have high landslide potential whereas P1 measurement point hadvalue G=2.0410 with medium soil character and flat or almost flat soil slope was classified as a area with low landslide potential.